Emerging Evidence of the Value of Culturally Specific Organizations: Results of a Delphi and Consumer Voice Study - Curry-Stevens, Ann (Advances in Social Sciences Research Journal, 2021)
A set of culturally specific organizations in Portland, Oregon has been generating excellent results for clients and communities of color. Four of them have developed a collective impact initiative to reduce child poverty among communities of color, with backbone support from United Way, and the inclusion of one “culturally responsive” organization. This research seeks to answer, “How do these organizations achieve excellent results with clients of color?” Our answer, through a two-part Delphi and Consumer Voice study, identifies a far-ranging set of assets, only part of which are staffing characteristics. These assets have been affirmed by a statistically significant survey of consumers, encompassing the following nine domains: being community embedded, creating a culture of success, being responsive to community needs, advocating to improve community and client success, being culturally relevant, and providing a comprehensive continuum of services. Delivery attributes include relying heavily on a rich relationship model, being inclusive, and having staff be personally invested in client success. Clients confirmed that all nine domains are important to their lives, and rated their overall satisfaction with the organizations at 92.7%, far above the published national average of 77%. The paper concludes with a synthesis of the study’s relevance for policy makers, funders and practitioners.